2007
DOI: 10.1038/sj.jcbfm.9600330
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 Compromises Blood–Brain Barrier Integrity and Enhance Monocyte Migration across Blood–Brain Barrier: Implication for Viral Neuropathogenesis

Abstract: Human immunodeficiency virus-1 (HIV-1) encephalitis is characterized by brain infiltration of virus-infected monocytes and macrophages. Cellular products and viral proteins secreted by infected cells likely play an important role in blood-brain barrier (BBB) impairment and the development of HIV-1-associated dementia (HAD). We previously demonstrated that HIV-1 envelope glycoprotein gp120 induces toxicity and alters expression of tight junction proteins in human brain microvascular endothelial cells (HBMECs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
200
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(207 citation statements)
references
References 68 publications
1
200
0
2
Order By: Relevance
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 99%
“…In CNS, CCR5 expression has been identified in microglia and brain endothelial cells (28,(55)(56)(57)(58)(59). We and others had shown that CCR5 was normally expressed on brain endothelial cells at lower level (28,57).…”
Section: Discussionmentioning
confidence: 99%
“…37 Previously, HIV-1 has been proposed to disrupt the integrity of brain endothelial cells, which possess tight junction structures as barrier components similar to those of HRPE cells. 17,[38][39][40][41] Other viruses, such as rotavirus and astrovirus, as well as some bacteria, are known to increase intestinal permeability by disrupting tight junctions as part of their pathogenesis. [21][22][23] Here we show that HIV-1 could also induce disruption of tight junction structures in HRPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with other results showing that HIV-1 gp120 downregulates the expression of tight junction proteins in the blood-brain barrier in a manner similar to the effect of HIV-1 gp120 on HRPE cells possessing well-developed tight junctions. 38,44 Viral infection is often associated with inflammation. Therefore, we next pointed out that the D407 monolayer is induced to release IL-6 and MCP-1 on exposure to HIV-1 (Figures 5a and b).…”
Section: Discussionmentioning
confidence: 99%
“…The type-IV pili of N. meningitides, on the other hand, stimulates the b2-adrenoceptor/b-arrestin signaling pathway in endothelial cells, leading to recruitment of the Par3/Par6/PKCz polarity complex and delocalization of junctional proteins which result in anatomical gaps that are used by the bacteria to penetrate into the CNS (Coureuil et al 2009(Coureuil et al , 2010. Human immunodeficiency virus (HIV) envelope glycoprotein gp120 has also been shown to increase BBB permeability by interacting with endothelial trans-membrane coreceptor CCR5 and CXCR4 (Kanmogne et al 2007). …”
Section: Paracytosismentioning
confidence: 99%